Probable second event due to SARS-CoV-2: 12 cases (Actualizaciones en Sida e Infectología, 2021)
As COVID-19 pandemic progresses, patients with a second confirmed episode by reverse transcription-polymerase chain reaction (RT PCR) compatible with reinfection reveals the lack of recommendations for its approach.A multicenter retro-prospective descriptive work was done of a series of 12 cases evaluated between June 1, 2020 and October 20, 2020. In this study, 10 out of 12 cases presented the second episode occurred in less than 90 days.Due to the diagnosing reinfection complexity, its confirmation is not available in the daily practice, this requires studies, which include viral strains genomic comparisons involved in both episodes, ARN determination infectivity by viral culture and molecular analysis.It is necessary to establish operational and clinical algorithms definitions to assist second episodes.
Keywords: SARS-CoV-2; COVID-19; coronavirus; reinfection